Reconfiguring Human, Nonhuman and Posthuman in Literature and Culture - Sanna Karkulehto; Aino-Kaisa Koistinen; Essi Varis (Routledge, 2020)
The time has come for human cultures to seriously think, to severely conceptualize, and to earnestly fabulate about all the nonhuman critters we share our world with, and to consider how to strive for more ethical cohabitation. Reconfiguring Human, Nonhuman and Posthuman in Literature and Culture tackles this severe matter within the framework of literary and cultural studies. The emphasis of the inquiry is on the various ways actual and fictional nonhumans are reconfigured in contemporary culture – although, as long as the domain of nonhumanity is carved in the negative space of humanity, addressing these issues will inevitably clamor for the reconfiguration of the human as well.The Open Access version of this book, available at https://www.taylorfrancis.com/books/reconfiguring-human-nonhuman-posthuman-literature-culture-sanna-karkulehto-aino-kaisa-koistinen-essi-varis/e/10.4324/9780429243042, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.